Functional alterations and transcriptomic changes during zebrafish cardiac aging - Shao, Xuelian; Fu, Yu; Ma, Jinmin; Li, Xueyu; Lu, Chenqi; Zhang, Ruilin (Biogerontology (Dordrecht), 2020)
Aging dramatically increases the risk of cardiovascular diseases in human. Animal models are of great value to study cardiac aging, and zebrafish have become a popular model for aging study recently. However, there is limited knowledge about the progression and regulation of cardiac aging in zebrafish. In this study we first validated the effectiveness of a panel of aging-related markers and revealed their spatial-temporal specificity. Using these markers, we discovered that cardiac aging in zebrafish initiated at mid-age around 24 months, followed by a gradual progression marked with increased DNA damage, inflammatory response and reduced mitochondrial function. Furthermore, we showed aging-related expression profile change in zebrafish hearts was similar to that in rat hearts. Overall, our results provide a deeper insight into the cardiac aging process in zebrafish, which will set up foundation for generating novel cardiac aging models suitable for large scale screening of pharmaceutical targets.